Jalaram Rice Mills Private Limited : Vishal H Mistry's dilemma - Varma, Poornima, active 2019; Jena, Sanjay Kumar (London : Indian Institute of Management, Ahmedabad, 2019)
In December 2019, Vishal H Mistry, the founder of Jalaram Rice Mills Private Limited (JRMPL), a rice-exporting firm in Ahmedabad, is facing some dilemmas concerning the export of rice. Currently, the firm is exporting non-basmati rice to Russia and South Africa. He received a bulk order for non-basmati rice from a new Russian firm. Based on his experience in the field, bulk orders are always risky, as the likelihood of the order getting cancelled in the last moment could put him at very high risk.Similarly, he is confused about the selling price of the rice. Compared to that between India and South Africa, the exchange rate between India and Russia was experiencing significant fluctuations in recent years. The appreciation of the Indian currency against that of the importing countries made the export costlier for Mistry. To make matters worse there was severe price competition in the importing markets. Since Mistry is a small exporter, he does not have much ability to reduce the price due to a lack of monopoly in the importing market. Therefore, Mistry is a price-taker and not a price-maker in the world market. Will he accept the order? If so, at what price?
Originally Published InVarma, P., & Jena, S. (2019). Jalaram Rice Mills Private Limited: Vishal H Mistry's Dilemma. IIMA/CMA0820. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Rice trade -- India -- Ahmadābād -- Case studies